The reaction of captive Mallard to grain treated with a commercial bird repellent - Kear, Janet (Wildfowl, 1965)
Wildfowl predation presents a very minor problem to agriculture as a whole in Britain, and only at certain times and in certain places does it become necessary to limit their activities (Kear, 1963). It is recognised that the application of a substance to a crop which will render it unattractive but not kill would be very advantageous, but the study of chemical protection against birds is still in its early stages. A variety of substances relying on the sense of taste, smell, touch or pain has been tried unsuccessfully with ducks in America (Neff and Meanley, 1956); whole barely soaked in gum turpentine and in kerosene was completely eaten and the commercial American repellent Pestex, dusted on to the grain, did not even slow the birds’ feeding rate. However, Neff and Meanley (1957) and Neff, Meanley and Brunton (1957) claimed consistent success against grackles, cowbirds, redwings and other birds when anthraquinone was used at heavy levels. Later, Duncan (1963) reported the reactions of feral pigeons to seven active ingredients of commercial repellents in solution. All solutions, with the exception of anthraquinone, produced a significant reduction of fluid intake and beta-naphthol was markedly rejected. Duncan pointed out that, although insoluble anthraquinone showed no repellent action when tested in this way, this does not mean that it is valueless when used as a powder. Anthraquinone (a harmless, yellow crystalline ketone, C(6)H(4)(CO)(2)C(6)H(4)) is in fact a basic ingredient of a German-made bird repellent marketed in Britain as Morkit. At the Wildfowl Trust, a few preliminary tests have been made in which four caged hand-reared Mallard were offered grain treated with Morkit.